Penilaian Hadith-Hadith Al-Khamru Dalam Kitab Tanbih Al-Ghafilin Oleh Sheikh Abdullah Bin Abdul Mubin - Mohd. Fauzi Mohd. Amin; Abdulloh Salaeh; Nidzamuddin Zakaria; Amran Abdul Halim; Syed Najihuddin Syed Hassan; Walid Mohd Said; Mahsor Yahya (Universiti Sains Islam Malaysia, 2024)
Proceedings of the 7th International Prophetic Conference (SWAN) 2020 FPQS,Universiti Sains Islam Malaysia, 29-30 October 2020 Paper No. BM019 385 - 400